2019
DOI: 10.1155/2019/6242745
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary Game Analysis of Chinese Food Quality considering Effort Levels

Abstract: Food safety accidents occur frequently, which has caused great harm to people’s health. With the consideration that food quality requires the joint efforts of all members of the food supply chain and that quality-improving efforts for food have a positive external effect, we focus on the quality-improving effort level, which is very important for food quality and safety. This paper builds an evolutionary game model and employs the replicated dynamic equation to study evolutionarily stable strategies of supplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…The present study provides a promising method for analyzing the behavioral strategy interaction between restaurants and OFD platforms to fill this gap. [21] and [34] are similar to our study; all these studies employ evolutionary game theory to analyze OFD-related problems, while the two studies focus on food quality and food waste recycling, respectively. In addition, evolutionary game theory is employed in modeling various problems, e.g., retailer competition [35], resource management [36], and bid evaluations [37], [38].…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…The present study provides a promising method for analyzing the behavioral strategy interaction between restaurants and OFD platforms to fill this gap. [21] and [34] are similar to our study; all these studies employ evolutionary game theory to analyze OFD-related problems, while the two studies focus on food quality and food waste recycling, respectively. In addition, evolutionary game theory is employed in modeling various problems, e.g., retailer competition [35], resource management [36], and bid evaluations [37], [38].…”
Section: Literature Reviewmentioning
confidence: 86%
“…A solution to the change in restaurants' behavior is to punish restaurants if they insist on using SFP. Nevertheless, a series of studies have shown that it is not sensible for the government to directly supervise and punish restaurants [19]- [21]. Thus, cogovernance is introduced in implementing the ban.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary game analysis based on the behavior of participants has become one of the main tools of the analysis of food safety, this is because it can involve government, consumers, companies, and other subjects. Current studies from the perspective of the evolutionary game between the two participants mainly consist of games between the government and companies [ 28 ], and between food suppliers and manufacturers [ 29 ]; the studies from the perspective of tripartite participants mainly consist of games of governments, companies, as well as consumers [ 30 ].…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Further, Yang et al designed an evolutionary game model to study evolutionarily stable strategies of food suppliers and producers. eir results showed that the behavioral strategies are the hitchhiking benefits, the cost of quality-improving efforts, and the initial strategy [30]. According to Neuwirth et al, the response efficacy of consumers is positively correlated with communicating intentions and self-efficacy, but it demonstrates a negative relationship to perceived barriers [31].…”
Section: Food Safety Standards and Monitoring Evaluation In Localmentioning
confidence: 99%